What will it take for biofortification to have impact on the ground? Theories of change for three crop-country combinations - Johnson, Nancy L.; Guedenet, Hannah; Saltzman, Amy (International Food Policy Research Institute, 2015)
These theories of change were developed to help the HarvestPlus program deliver on its planned outcomes and impacts. HarvestPlus expects to contribute to the reduction in micronutrient deficiency among women and children in rural areas of developing countries through the breeding and dissemination of staple crop varieties with increased levels of key micronutrients. After ten years of breeding, economic, and nutrition research to develop and assess varieties and their potential impact on human nutritional outcomes, HarvestPlus is entering a third five-year phase focused on delivering micronutrient-rich varieties at scale in nine target countries. To support program design, implementation, and evaluation in the “delivery” phase of the HarvestPlus program (2014–2018), theories of change were developed for three crop-country combinations—maize in Zambia, beans in Rwanda, and cassava in Nigeria—to describe how HarvestPlus expects to contribute to the outcome of reducing inadequate micronutrient intake among women and children in different agricultural and socioeconomic contexts in which HarvestPlus works. The evidence supporting the assumptions and risks for each link in the pathway is summarized and assessed. The results show that for some parts of the impact pathway, outcomes and causal links are well defined and supported by evidence. In other areas, the program logic needs to be better articulated so that hypotheses can be formulated and evidence generated. Addressing these gaps through research, adaptations in delivery activities, and monitoring can increase the likelihood of achieving expected outcomes as well as improve the ability of HarvestPlus and other nutrition-sensitive agricultural programs to learn from current activities to inform a broader scaling up.